The only road - Diaz A.; Simon and Schuster Book (New York: Simon and Schuster Books, 2016)
'Twelve-year-old Jaime makes the treacherous journey from his in Guatemala to his older brother in New Mexico after his cousin is murdered by a drug cartel '
Junior Fiction-Juvenile